Pediatric living donor liver transplantation with non-anatomical portal vein reconstruction in idiopathic extrahepatic portal vein thrombosis - Tri Hening Rahayatri; Harsya Dwindaru Gunardi; Rusdah Binti Muhammad Amin; Damayanti Sekarsari; Marini Stephanie; Sastiono Soedibyo; Seisuke Sakamoto; Mureo Kasahara (Elsevier, 2020)
A 13-year-old boy had a history of recurrent hematemesis and melena since the age of 2 years. Owing to recurrent bleeding, he had undergone several endoscopic ligation procedures and had received regular blood transfusions over the last 7 years. Doppler ultrasonography showed extrahepatic portal vein thrombosis, while the hepatic vein was not visualized. Abdominal computed tomography confirmed cavernous transformation in the liver hilum. Liver biopsy revealed fibrosis. A diagnosis of extrahepatic portal vein obstruction (EHPVO) with portal hypertension was established. Living donor liver transplantation (LDLT) was performed owing to recurrent gastrointestinal bleeding and liver fibrosis. The liver graft was obtained from the patient's father, utilizing segments 2, 3, and 4 (graft-to-recipient weight ratio: 0.84%). Portal vein reconstruction using native internal jugular vein and external iliac vein was achieved with non-anatomical anastomosis due to the lack of availability of sizable superior mesenteric vein. The postoperative course was uneventful.We successfully performed LDLT with unusual portal vein reconstruction in a patient with EHPVO. Multiple interposition grafts were used to obtain adequate inflow from the splenorenal shunt. LDLT remains the last resort in such cases as other surgical procedures (such as Meso-Rex bypass) are not feasible.